THE EFFECT OF THE PLYOMETRIC TRAINING METHOD ON THE SHOOTING ABILITY OF SSB PPFC JUNIOR U 16 MEGANG SAKTI MUSI RAWAS REGENCY - Muhammad Agung Nur Aziz Agung; Yuli Febrianti; Hengky Remora (International Journal of Educational Review, 2026)
The purpose of this study is to determine the Influence of the Plyometric Training Method on the Shooting Ability of SSB PPFC Junior U 16 Players Megang Sakti Musi Rawas Regency. This study is Pre-experimental using a research design is One Group Pretest-Posttest Design. The subject in the study is SSB PPFC Junior U 16 players and the population in this study is 24 people. The sampling technique is by means of total sampling and the variables in this study are shooting ability. Data analysis uses t-test statistics. The instrument used for the initial test was the shooting ability exercise was 78.33 and the final test was 112.50, from the results of the test the difference in shooting ability was 17.097 to the calculated t-value of 4.141 with a table t-value of 1.714. At the significance level of 0.05 so that the tcount > ttable. So it can be concluded that there is an influence on the shooting ability of SSB PPFC Junior U 16 Megang Sakti Players in Musi Rawas Regency and the results have increased.